2009
DOI: 10.1111/j.1479-828x.2009.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Participant evaluation of the RANZCOG Fetal Surveillance Education Program

Abstract: After a 'needs assessment', in 2004 the Royal Australian and New Zealand College of Obstetricians and Gynaecologists developed and introduced the Fetal Surveillance Education Program (FSEP) to provide high quality education to all clinicians caring for labouring women in Australia and New Zealand. A formal evaluation of the program was planned from the inception of FSEP. We report here the participant feedback from the first 4439 participants in 2004-2006. Overall, FSEP was considered a high quality resource, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…These findings are likely to be related to levels of precourse knowledge and expertise, 23 but support similar findings of a previous Australian study 24 which found that completion of an intrapartum fetal surveillance programme did not necessarily increase confidence to interpret CTG traces.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are likely to be related to levels of precourse knowledge and expertise, 23 but support similar findings of a previous Australian study 24 which found that completion of an intrapartum fetal surveillance programme did not necessarily increase confidence to interpret CTG traces.…”
Section: Discussionsupporting
confidence: 85%
“…Nine studies were evaluated at Kirkpatrick level 1, 10,12–19 14 studies were evaluated at level 2, 9–11,13–15,20–27 five studies were evaluated at level 3, 12,20–22,28 and two studies were evaluated at level 4 20,28 …”
Section: Resultsmentioning
confidence: 99%
“…Of the nine papers categorised as level 1, five used questionnaires 10,16–19 . Four papers reported the data obtained, 10,16,18,19 and the others described positive responses 12,14,15,17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the VASM survey results, positive feedback on the value of the case note review booklets, as well as a perceived improvement in the local level of care was reported 20. Various examples of improvements from learning outcomes in other clinical audits and registries to which VASM could refer included the observed changes in surgical practices in Western Australia,21 the development of risk scores specific to Australian patients who underwent cardiovascular surgery,22 the surgical outliers process embedded into the vascular audit system,23 providing training programmes within the health setting,24 25 improving communication between medical and surgical teams,26–28 ensuring surgeons in Australia meet high standards of clinical practice and patient care29 and the New Zealand perioperative mortality review committee activity 30. A recent review by Watters et al 31 has shown that there is value in establishing a predictive model to reduce perioperative mortality, but acknowledges that unless mortality audits examine the circumstances surrounding deaths improvements will not occur.…”
Section: Discussionmentioning
confidence: 99%